No front da vida : arte-fatos e afetos de uma comunidade em situação de rua em Cuiabá - Lopes, Eliete Borges (2016)
The thesis herein is the one that in Cuiabá there is a homeless community that inhabits the Bananal Island downtown and that this community possesses a self-organization whose starting point is the art-facts and affections it mobilizes. This phenomenon was described from exploratory field research and has recurred to dialogues with the homeless inhabitants and the description of the phenomena that comprise the community that inhabits the Bananal Island. The art-facts and affections are a means of expression of an entire material and immaterial culture that involves the life of a homeless population that inhabits the Bananal Island. The main interlocutor in this research was Andreia, the Fragrant, who died this year. The research reveals that even living under the auspices of vulnerability, the Bananal Island community manages to resist phenomena like poverty and violence. The research path has developed from the phenomenon of interaction between the homeless population and the many elements present in the community, be it the architectonic dimension, the graffiti and performance acts of life on the streets. The appropriation dimensions and the transformation of culture and of life itself through art-facts and affections present in the community assure inhabiting the streets like a resistance process and indicate the possibility of a new episteme for understanding the perspective of a homeless population. A streets episteme and, above all, a Southern streets episteme start insinuating a trajectory in which the homeless population as a protagonist in the process of inhabiting the streets reveals its critical-educative dimension.